1986
DOI: 10.2307/1467704
|View full text |Cite
|
Sign up to set email alerts
|

Filter-Feeding in Corbicula fluminea and Its Effect on Seston Removal

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 17 publications
1
51
0
3
Order By: Relevance
“…This drop in the clearance rate with low food levels stands in contrast to theory on the functional response of filter feeders, which predicts high rates at low food levels and decreasing rates with increasing food levels beyond a threshold level (incipient limiting level) in order to balance ingestion rate (e.g., Jeschke et al 2004). It has also been shown that food concentration and clearance rates were inversely related in C. fluminea (Lauritzen 1986). The drop in clearance rate found here can also not be explained by decreasing temperature during the end of summer (compare Viergutz et al 2007), because the temperatures at that time were similar to those recorded in May and June, during which high clearance rates were measured.…”
Section: Shell Length Increase Versus Body Mass Decrease During Starvmentioning
confidence: 96%
“…This drop in the clearance rate with low food levels stands in contrast to theory on the functional response of filter feeders, which predicts high rates at low food levels and decreasing rates with increasing food levels beyond a threshold level (incipient limiting level) in order to balance ingestion rate (e.g., Jeschke et al 2004). It has also been shown that food concentration and clearance rates were inversely related in C. fluminea (Lauritzen 1986). The drop in clearance rate found here can also not be explained by decreasing temperature during the end of summer (compare Viergutz et al 2007), because the temperatures at that time were similar to those recorded in May and June, during which high clearance rates were measured.…”
Section: Shell Length Increase Versus Body Mass Decrease During Starvmentioning
confidence: 96%
“…Filtration by clams is often sporadic and varies in rates and timing of uptake between individuals (Lauritsen 1986). Evaluation of pH and clam shell effects and the characterization of viral titres within short time intervals suggest that the filtrating behaviour of the C. fluminea was likely the dominant process producing the titre reduction.…”
mentioning
confidence: 99%
“…Many stream organisms are adapted to feed on seston (e.g. Wallace and Merritt 1980;Lauritsen 1986), and transport of seston is an essential linkage along the continuum of stream ecosystems in a river system (Vannote et al 1980). Wotton (1984) suggested that two processes generate seston in streams: primary generation by breakdown of large particles, chiefly by insects (e.g.…”
mentioning
confidence: 99%